Analytical methods for gelatin differentiation - S., Amira Aqilah; Tukiran, Nur Azira; G., Haizatul Hadirah; Nurul Azarima, M. A.; Siti Nur Syahirah, Z. (HH Publisher, 2019)
Gelatin differentiation in edible products has been a debate over the years with respect to health and religious concerns. Researchers had performed various of studies in tackling this issue thus various of analytical methods for gelatin differentiation were developed. Such analytical methods mentioned involving several instruments and techniques including chromatography, molecular, electrophoresis, immunochemical and spectroscopy had been developed for finding the most accurate method in gelatin differentiation. However, with every method developed there will always be advantages and limitations. The present paper provides review on the recent method for gelatin differentiation as well as the advantages and disadvantages of each available method.